PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.3 SMP DWIPA ABADI SUNGAI GUNTUNG INDRAGIRI HILIR - Radiance Agusfita; Jalinus '; Armis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve learning process and increase the mathematic learning outcomes by implying stuctural approach to cooperative learning think pair square model. Subjects of this research are the students of VII.3 SMP Dwipa Abadi Sungai Guntung Indragiri Hilir in the academic year 2016/2017. Total number of participant are 24 whose academic achievement are heterogen. This research have two cycles, each have four stages: planning, implementation, observation, and reflection. Each cycles ended by daily examination (UH). The data collected by observation and examination. The data analised by narative descriptive and statistical descriptive. The implementation called success if there’s positive improvement of the learning process and the number of students who reach KKM increase from the basic score to daily examinations (UH I to UH II). The research result from the observation sheets shows that teacher and student activities are improving after the model implemented. More than half students actively participated in the learning process, as in group discussion, presented their works, responded to other group, and sum up the learning conclusion. The number of students whose achieved basic score of KKM, UH I), and UH II are 10 students (29,17%), 13 student (54,17%) and 18 student (18 75%). This research shows that implying stuctural approach to cooperative learning think pair square model can improve learning process and increase mathematic learning outcomes for students of VII.3 SMP Dwipa Abadi Sungai Guntung Indragiri Hilir on odd semester of 2016/2017, to the basic competence (2.1) Recognize the algebra and its elements, (2.2) Perform the operation on the algebra, and (2.3 Solve linear equations of one variable.